2005
DOI: 10.1371/journal.pcbi.0030058.eor
|View full text |Cite
|
Sign up to set email alerts
|

Structural Descriptors of gp120 V3 Loop for the Prediction of HIV-1 Coreceptor Usage

Abstract: HIV-1 cell entry commonly uses, in addition to CD4, one of the chemokine receptors CCR5 or CXCR4 as coreceptor. Knowledge of coreceptor usage is critical for monitoring disease progression as well as for supporting therapy with the novel drug class of coreceptor antagonists. Predictive methods for inferring coreceptor usage based on the third hypervariable (V3) loop region of the viral gene coding for the envelope protein gp120 can provide us with these monitoring facilities while avoiding expensive phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 37 publications
0
9
0
3
Order By: Relevance
“…It has been shown that intrahost evolution of the V3 loop structure is highly diverse and structurally flexible throughout the infection (Watabe et al, 2006). Therefore, structural modifications seem to be related to immune pressures and interactions with the cell coreceptor (Sander et al, 2007). Indeed, monoclonal antibodies directed against the D19 epitope within the V3 region neutralize only the X4 variants (Lusso et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that intrahost evolution of the V3 loop structure is highly diverse and structurally flexible throughout the infection (Watabe et al, 2006). Therefore, structural modifications seem to be related to immune pressures and interactions with the cell coreceptor (Sander et al, 2007). Indeed, monoclonal antibodies directed against the D19 epitope within the V3 region neutralize only the X4 variants (Lusso et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, monoclonal antibodies directed against the D19 epitope within the V3 region neutralize only the X4 variants (Lusso et al, 2005). Consequently, inaccessibility of this antibody to R5 might indicate that there are significant V3 loop conformational differences between these two variants (Sander et al, 2007). In fact, it has been demonstrated that intricate electrostatic interactions occur among amino acid residues in order to preserve the proper tertiary structure of the V3 loop (Rosen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Isso explica porque apenas alguns indivíduos desenvolvem cepas X4 (Mild et al, 2009 (Poon et al, 2007;Rosen et al, 2006;Sander et al, 2007). Ainda não está claro se o aparecimento de aminoácidos básicos nas posições 11 e 25 é suficiente ou mesmo necessário para a emergência de cepas X4, mas diferenças intrínsecas na alça V3 entre os subtipos podem levar a diferenças na emergência das cepas X4 e é provável que a troca do tropismo seja um processo gradual de acúmulo de mutações (Hughes e Nelson, 2009;Jensen et al, 2003).…”
Section: A Mudança De Tropismounclassified
“…Ainda não está claro se o aparecimento de aminoácidos básicos nas posições 11 e 25 é suficiente ou mesmo necessário para a emergência de cepas X4, mas diferenças intrínsecas na alça V3 entre os subtipos podem levar a diferenças na emergência das cepas X4 e é provável que a troca do tropismo seja um processo gradual de acúmulo de mutações (Hughes e Nelson, 2009;Jensen et al, 2003). (Braun e Wiesmann, 2007;Sander et al, 2007;Sierra et al, 2007).…”
Section: A Mudança De Tropismounclassified
See 1 more Smart Citation